2014
DOI: 10.1128/iai.01569-14
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor of Activated T Cells Regulates Neutrophil Recruitment, Systemic Inflammation, and T-Cell Dysfunction in Abdominal Sepsis

Abstract: The signaling mechanisms regulating neutrophil recruitment, systemic inflammation, and T-cell dysfunction in polymicrobial sepsis are not clear. This study explored the potential involvement of the calcium/calcineurin-dependent transcription factor, nuclear factor of activated T cells (NFAT), in abdominal sepsis. Cecal ligation and puncture (CLP) triggered NFAT-dependent transcriptional activity in the lung, spleen, liver, and aorta in NFAT-luciferase reporter mice. Treatment with the NFAT inhibitor A-285222 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…These data are supported by the increased NF-κB and p-IκB-α levels in the pancreas of septic WT and SP-D KO mice. Our findings are consistent with previous studies that demonstrated increased TNF-α and IL-6 in the serum during polymicrobial sepsis by CLP 57 58 . Additionally, in vitro experiments with isolated islet cultures stimulated by LPS demonstrated SP-D function in the modulation of inflammatory cytokine production in the islet cells.…”
Section: Discussionsupporting
confidence: 93%
“…These data are supported by the increased NF-κB and p-IκB-α levels in the pancreas of septic WT and SP-D KO mice. Our findings are consistent with previous studies that demonstrated increased TNF-α and IL-6 in the serum during polymicrobial sepsis by CLP 57 58 . Additionally, in vitro experiments with isolated islet cultures stimulated by LPS demonstrated SP-D function in the modulation of inflammatory cytokine production in the islet cells.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, several studies using NFAT inhibitors for different immune-related disease models support that inhibition of the NFAT pathway can attenuate an immune response. [27][28][29][30][31][32] Moreover, among individuals with Down syndrome, the inhibition of the NFAT pathway (partly via overexpression of DYRK1A and DSCR1 due to trisomy 21) 33,34 is hypothesized to be related to the cardiac, neurologic, and immunologic defects associated with Down syndrome, 34 and individuals with Down syndrome may have attenuated antibody responses to several vaccine antigens. 35 Based on this role of the NFAT pathway in Down syndrome, and on our finding of a higher incidence of asparaginase hypersensitivity among those carrying the NFATC2 variant, we hypothesized that Down syndrome patients might have a lower incidence of asparaginase hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…An overall weaker response in athymic rats can be explained by their lack of Th17 regulatory T helper cells, as neutrophil recruitment can be mediated by IL-17 and nuclear factor of activated T cells (NFAT). 23,24 It was also found that strong infiltration was not observed until day 3 in athymic rats but started at day 1 in immunocompetent rats (Figure 3). The delayed response in athymic rats may be caused by the administration of Meloxicam for pain control for all the animals.…”
Section: Discussionmentioning
confidence: 84%